Effectiveness of multimedia-based instruction that emphasizes molecular representations on students' understanding of chemical change - Ardac, Dilek; Akaygun, Sevil (Journal of research in science teaching, 2004)
The present study makes use of the capabilities of computerized environments to enable simultaneous display of molecular representations that correspond to observations at the macroscopic level. This study questions the immediate and long‐term effects of using a multimedia instructional unit that integrates the macroscopic, symbolic, and molecular representations of chemical phenomena. Forty‐nine eighth graders received either multimedia‐based instruction that emphasized molecular representations (n = 16), or regular instruction (n = 33). Students who received multimedia‐based instruction that emphasized the molecular state of chemicals outperformed students from the regular instruction group in terms of the resulting test scores and the ease with which they could represent matter at the molecular level. However, results relating to the long‐term effects suggest that the effectiveness of a multimedia‐based environment can be improved if instruction includes additional prompting that requires students to attend to the correspondence between different representations of the same phenomena. © 2004 Wiley Periodicals, Inc. J Res Sci Teach 41: 317–337, 2004